Upper trunk block for shoulder analgesia with potential phrenic nerve sparing: a preliminary anatomical report. Issue 9 (September 2019) - Cros Campoy, José; Domingo Bosch, Oscar; Pomés, Jaume; Lee, Jing; Fox, Ben; Sala-Blanch, Xavier
Abstract : Background and objectives: Ipsilateral phrenic nerve palsy (PNP) is an undesirable side of conventional approaches to interscalene brachial plexus blocks. The purpose of this study was to demonstrate whether or not the phrenic nerve can be spared by dye when injected at the division of the upper trunk of the brachial plexus. Methods: Under ultrasound guidance, 5 mL of radiolabeled dye was injected between the anterior and posterior division of the upper trunk in two fresh, cryopreserved cadavers. CT scan analysis, cadaveric dissection, and cryosectioning were performed to examine the spread of the injectate. Results: We found staining of the injectate over the entire upper trunk with its anterior and posterior divisions, the suprascapular nerve under the omohyoid muscle and the lateral pectoralis nerve, and the C5 and C6 roots. The middle trunk was partially stained. There was no evidence of dye staining of the lower trunk, anterior aspect of the anterior scalene muscle, or the phrenic nerve. Conclusions: Our study offers an anatomical basis for the possibility of providing shoulder analgesia and avoiding a PNP.